2018
DOI: 10.1093/jas/sky185
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of renal calcium and phosphate transporting proteins by dietary nitrogen and/or calcium in young goats1

Abstract: In young goats, a reduction in dietary nitrogen (N) had an impact on mineral homeostasis although ruminants are able to recycle N effectively due to rumino-hepatic circulation. A solitary calcium (Ca) reduction stimulated calcitriol synthesis and Ca concentrations remained unchanged, whereas a dietary N reduction led to a decrease in calcitriol, which could not be prevented by a simultaneous reduction of N and Ca. In a previous study, it was shown that a reduced dietary N intake caused a decrease in intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This is in line with data from balance studies conducted with goat kids (Table 1). A concomitant decrease in dietary Ca and protein in these young animals caused a decrease in 1,25-(OH) 2 D 3 concentrations, resulting in a downregulation of TRPV5, CaBP D28K and NCX1 protein expressions (Firmenich et al, 2018).…”
Section: Renal Handling Of Calciummentioning
confidence: 93%
See 1 more Smart Citation
“…This is in line with data from balance studies conducted with goat kids (Table 1). A concomitant decrease in dietary Ca and protein in these young animals caused a decrease in 1,25-(OH) 2 D 3 concentrations, resulting in a downregulation of TRPV5, CaBP D28K and NCX1 protein expressions (Firmenich et al, 2018).…”
Section: Renal Handling Of Calciummentioning
confidence: 93%
“…A significant increase in NaPi IIa expression and a concomitant decrease in PTH receptor expression were observed in young goats (4 to 5 months) when dietary protein was diminished. The concentration of 1,25-(OH) 2 D 3 was reduced while PTH levels were not affected (Starke et al, 2013;Starke and Huber, 2014;Firmenich et al, 2018). The stimulation of NaPi IIa expression during a protein-reduced diet is not obvious.…”
Section: Renal Handling Of Phosphorusmentioning
confidence: 93%
“…The protein sequences were verified for their homology with NCBI Blast (see text footnote 1). Immunoblot assays detecting the expression of ERK1/2, NaPi IIa and Na + /K + ATPase proteins in caprine tissue were performed as described elsewhere (5,37). Membranes were incubated solely with the secondary antibody to ensure exclusive detection of specific signals.…”
Section: Tissue Extraction and Western Blot Analysismentioning
confidence: 99%
“…Previous studies have shown that goats fed reduced N diets had lower blood calcium (Ca) levels (4,5). In a study by Muscher and Huber (4), N-reduction also resulted in alterations in vitamin D metabolism.…”
mentioning
confidence: 99%
“…The opposite appears to be the case in humans [ 15 , 16 ]. However, while the expression of phosphatonin-related proteins is relatively well described in the kidneys of goats [ 17 , 18 , 19 ] and in the intestines of horses, goats and cattle [ 20 , 21 , 22 , 23 ], knowledge on the expression of phosphatonin-related proteins in the kidneys of most domestic species is lacking.…”
Section: Introductionmentioning
confidence: 99%